An econometric approach to aggregating multiple cardiovascular outcomes in German hospitals - Angela Meggiolaro; Carl Rudolf Blankart; Tom Stargardt; Jonas Schreyögg (The European Journal of Health Economics, 2022)
Objective: Development of an aggregate quality index to evaluate hospital performance in cardiovascular events treatment. Methods: We applied a two-stage regression approach using an accelerated failure time model based on variance weights to estimate hospital quality over four cardiovascular interventions: elective coronary bypass graft, elective cardiac resynchronization therapy, and emergency treatment for acute myocardial infarction. Mortality and readmissions were used as outcomes. For the estimation we used data from a statutory health insurer in Germany from 2005 to 2016. Results: The precision-based weights calculated in the first stage were higher for mortality than for readmissions. In general, teaching hospitals performed better in our ranking of hospital quality compared to non-teaching hospitals, as did private not-for-profit hospitals compared to hospitals with public or private for-profit ownership. Discussion: The proposed approach is a new method to aggregate single hospital quality outcomes using objective, precision-based weights. Likelihood-based accelerated failure time models make use of existing data more efficiently compared to widely used models relying on dichotomized data. The main advantage of the variance-based weights approach is that the extent to which an indicator contributes to the aggregate index depends on the amount of its variance.
Keywords: I11; 610; Quality of care; Hospital; Accelerated failure time model; Cardiovascular diseases